Improving an image retrieval system by integrating semantic features - Ion, A.L.; Stanescu, L.; Burdescu, D.; Udristoiu, S. (2008 Conference on Human System Interactions, 2008)
To develop image navigation systems, we need tools to realize the semantic relationship between user and database. In this paper, it is presented an indexing schema of images and a simple semantic vocabulary that permits to the user to introduce the cognitive dimension in the retrieval process. A lot of experiments, in which the human subjects had to group images into semantic categories and to explain the criteria for their choice, were realized. From these experiments, we identify the semantic categories (landscapes, animals, flowers, etc), the semantic indicators or intermediate descriptors and their visual characteristics.